EFFECT ADDEB ECONOMIC VALUE ADDED (EVA), EARNINGS, AND OPERATIONS OF RETURN FLOW MANUFACTURING COMPANY SHARES ARE REGISTERED IN THE BEI PERIOD 2004-2007 - Aprilia, Ari (Accounting, 2010)
EVA (Economic Value Adebb) is the added value produced by subtracting a company capital costs incurred as a result of investments made. Earnings represents net income before extraordinary accounts. Operating cash flow is cash flow from normal business operation which is the difference between profit and sales and after-tax cash operating expenses over operating revenues. While the stock return is the profit earned from ownership of shares of the investments made. The author would like to know the influence of EVA, earnings, and operating cash flows to stock return either partially or simultaneously. This research is an empirical study using data from 27 manufacturing companies in the sample period 2004 up to 2007. The data analysis technique used is by using t-test, F test, and R2.Dengan using SPSS version 15 obtained the following results: (1) EVA positive effect is not significant to return with a probability error rate 0.176 larger than the significant level expected that 0.050. (2) Earnings significant positive effect on stock return with a probability of 0.013 error rate significantly smaller than the expected level of 0.050. (3) Operating cash flow is not significant negative effect on stock return with a probability of 0.413 error rate significantly greater than the expected level of 0.050. (4) Together EVA, earnings, operating cash flow was not significant positive effect on stock return with a probability of 0.070 error rate greater than expected at a significant level of 0.050. Keyword : EVA, Earning, Stock, Manufacture